1997
DOI: 10.1073/pnas.94.16.8878
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response to long-term peripheral and central leptin infusion in lean and obese mice

Abstract: Recent data have identified leptin as an afferent signal in a negative-feedback loop regulating the mass of the adipose tissue. High leptin levels are observed in obese humans and rodents, suggesting that, in some cases, obesity is the result of leptin insensitivity. This hypothesis was tested by comparing the response to peripherally and centrally administered leptin among lean and three obese strains of mice: diet-induced obese AKR͞J, New Zealand Obese (NZO), and A y . Subcutaneous leptin infusion to lean mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
674
5
14

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(729 citation statements)
references
References 43 publications
(68 reference statements)
36
674
5
14
Order By: Relevance
“…A decrease in the ratio CSF-to-serum leptin concentrations suggested that a failure at the level of the transport from blood to CSF could be the cause of leptin resistance in obese humans [8]. This also has been reported in another experimental model with leptin resistance such as the New Zealand obese mice [10]. These animals respond to i.c.v.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A decrease in the ratio CSF-to-serum leptin concentrations suggested that a failure at the level of the transport from blood to CSF could be the cause of leptin resistance in obese humans [8]. This also has been reported in another experimental model with leptin resistance such as the New Zealand obese mice [10]. These animals respond to i.c.v.…”
Section: Discussionmentioning
confidence: 64%
“…Leptin transport across the bloodbrain barrier and/or the blood-cerebrospinal fluid barrier, any of the steps of the hormonal signal transduction cascade in the hypothalamus or even steps beyond the leptin-sensitive neurons are possible targets to be altered in leptin resistance states such as obesity and ageing. Alteration of leptin transport across the blood-brain barrier has been proposed to occur in obese humans [8,9], in New Zealand obese mice [10] and in diet-induced obese mice [11]. An impairment in the leptin signal transduction cascade has been shown in the old Fisher 344XBN rat [12,13].…”
mentioning
confidence: 99%
“…[34][35][36] Although leptin resistance was reported in obesity, 37 reduced Arc NPY content in our mice at 10 weeks may represent a possible response to the hyperleptinemia. The decreased NPY concentrations in the AH and PH may reflect a decrease in NPY release from the Arc.…”
Section: Npy Cck and Adipokines In Dietary Obesity Mj Morris Et Almentioning
confidence: 67%
“…Most obese humans and rodents have elevated serum leptin and impaired physiological responses to exogenously administered leptin, and are hence considered leptin-resistant [1][2][3][4][5]. In contrast, in lean rodents leptin evokes potent anorectic and thermogenic responses and produces marked lipopenia and weight reduction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%